Conversations with Milošević - Roberts, Ivor, 1946- (The University of Georgia Press, 2016)
"A portrayal of the nightmare world and personalities of Balkan politics and war by a diplomat with unparalleled access to Milošević, the man at the heart of the darkness. It analyses where the West went wrong in terms of waging a war for regime change and in recognizing Kosovo despite UN resolutions to the contrary"--Provided by publisher